Effect of pre-sowing seed bio-inoculation on seed yield, its contributing characters and subsequent seed quality of barley (Hordeum vulgare) - PRASAD, BIRENDRA; PRASAD, RAJENDRA; PRASAD, SHAMBHOO; KUMAR, SUNIL (The Indian Journal of Agricultural Sciences, 2014)
A study was carried out to examine the effect of pre-sowing seed inoculation with Pseuodomonas fluorescens and Trichoderma harzianum either singly (@ 4g, 6g, 8g per kg seed) or in combination with both bio-inoculants (@ (2+2)g, (3+3)g, (4+4) g/kg seed) on growth, seed yield and subsequent seed quality of barley. There was significant difference among different seed bio-inoculation treatment over un-inoculated control with regard to field emergence, root length, plant height, ear length, number of seeds per ear, 1000-seed weight and seed yield/ha under field trial and also for subsequent seed quality, i e germination, radicle, plumule and seedling length, fresh and dry weight of seedlings and vigour index (I&II) under laboratory experiment. Seed yield and its contributing characters as well as subsequent seed quality were found to be higher as the amount of P. fluorescens and T. harzianum increased from 4 to 8 g/kg either singly or in combination of both bio-inoculants. The bio-inoculants mixture showed greater influence on seed yield and quality over seeds treated either with P. fluorescens and T. harzianum and both bio-inoculants mixture @ (4+4) g/kg seeds had maximum influence on characters studies under field as well as laboratory experiment.